Wage bargaining in Germany. The role of works councils and opening clauses - Ellguth, Peter; Gerner, Hans-Dieter; Stegmaier, Jens (Nürnberg, 2012)
"German employment relations are characterized by a distinct dual system: First, working conditions and wages are determined by industry level collective bargaining agreements. Second, on the establishment level the works council is responsible for employer-employee negotiations. But since the mid-1980s more and more areas of regulation were transferred from the industry to the establishment level using so called opening-clauses. Our analysis relies on rich German establishment data and reveals new insights in the institutional machinery of wage bargaining: While the existence of such clauses is related to higher wages (11 %), their application results in wages cuts of roughly the same size. Regarding works councils our results suggest that they are able to prevent negative wage effects of opening clauses on average."